Implementation of Allo-Repition Strategy to Improve Learners’ Participation in Speaking Activities at Speaking II Course of English Department STAIN Kerinci - Novri Pahrizal (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
This study focused on implementation of allo-repition strategy to improve learners’ participation in speaking activities. It was a classroom action research (CAR) which conducted in two cycles at speaking II course of English department STAIN Kerinci wherein in this study, the writer only conducted at one class of three consisted of 33 learners. The data were collected by using speaking test, observation, questionnaires and interview. The collected data were analyzed quantitatively and qualitatively to know the process learning and result of implementing allo-repition strategy. The results of data analysis from observations show the improvement of learners’ involvement in learning process. The data from learners’ speaking activities show the improvements in terms of numbers of exchanges the learners could produce in a conversation, learners’ turn-taking, and learners’ back-channeling. The data from questionnaires and interview show the improvement of learners’ perception toward learning speaking by using Allo-Repetition strategy and the technique of lecturer in teaching. The result of this study indicates that it better improves learners’ participation in speaking activities.